Collaboration between Mountain and Lowland Farms Decreases Environmental Impacts of Dairy Production: The Case of Swiss Contract Rearing - Marton, Silvia M. R. R.; Lüscher, Gisela; Corson, Michael S.; Kreuzer, Michael; Gaillard, Gérard (Frontiers in Environmental Science, 2016)
Mountain farming areas are associated with high nature value and offer attractive landscapes, but farming in these areas is less viable than farming in more favorable regions. Consequently, there is a threat of land abandonment. Additionally, due to lower productivity of mountain farms, their products often bear a higher environmental burden than those from other areas. An optimal division of labor between mountain farms and farms in more favorable regions based on comparative advantages could help maintain attractive landscapes and reduce environmental impacts of agricultural production. An established Swiss contract rearing system, in which dairy farms from the agriculturally favorable lowlands collaborate with heifer rearing farms in the mountains, represents a promising approach for such a division of labor. In this system, the intensive phase of dairy production is performed in the lowlands, while the less intensive phase is performed in the mountains. Here, we analyzed a sample of 16 farms to compare the contract rearing system to a situation in which both, mountain and lowland farms produce milk and rear their own restocking animals. We performed a life cycle assessment to quantify environmental impacts of the dairy production systems, assessing environmental impacts both per kg of milk and per hectare of agricultural area. This assessment was supplemented with analysis of the workload of the farms, since increased work efficiency is one reason that farmers engage in contract rearing. Workload was calculated with a workload budgeting tool. We found that collaboration reduced environmental impacts as well as the workload per kg of milk. Collaboration had no effect on environmental impacts per hectare of agricultural area or the workload on lowland farms, while on mountain farms the environmental impacts and workload were reduced. In particular, reduction in environmental impacts of mountain farms is expected to foster the high nature value of this farmland and the provisioning of important ecosystem services. This case study of a contract rearing system thus illustrates how collaboration based on comparative advantages can benefit both environmental impacts of agricultural products and the high nature value of agriculturally less favorable farmland.